Incidence and risk factors for reactivation from resolved hepatitis B virus in rheumatoid arthritis patients treated with biological disease‐modifying antirheumatic drugs. (18th October 2018) - Watanabe, Toshiyuki; Fukae, Jun; Fukaya, Shinji; Sawamukai, Norifumi; Isobe, Masato; Matsuhashi, Megumi; Shimizu, Masato; Akikawa, Kazumasa; Tanimura, Kazuhide; Atsumi, Tatsuya; Koike, Takao
Abstract: Aim: To identify the incidence and risk factors for hepatitis B virus (HBV) reactivation in rheumatoid arthritis (RA) patients with resolved HBV receiving biological disease‐modifying antirheumatic drugs (bDMARDs). Method: Rheumatoid arthritis patients in whom bDMARD therapy was initiated in our departments from April 2009 to July 2016 were reviewed. The patients diagnosed with resolved HBV and whose HBV‐DNA levels had been repeatedly measured were enrolled. The endpoint was HBV reactivation (a positive conversion of HBV‐DNA or unquantifiable cases with positivity <20 IU/mL). Nucleic acid analogues (NAAs) were administered when the HBV‐DNA levels increased beyond 20 IU/mL. The associations between HBV reactivation and the clinical findings were retrospectively analyzed. Results: One hundred and fifty‐two RA patients with resolved HBV were enrolled; 133 (88%) patients had antibodies against HBV surface antigen (anti‐HBs). The medicines that were administered included: abatacept (n = 29), golimumab (n = 26), etanercept (n = 25), tocilizumab (n = 25), adalimumab (n = 19), infliximab (n = 17) and certolizumab pegol (n = 11). During the observation period (15 [interquartile range 4.0‐34] months), 7 (4.6%) patients developed HBV reactivation. In 5 of these patients, the HBV‐DNA levels became negative or remained at <20 IU/mL (+) without NAA therapy. HBV‐DNA levels of >20 IU/mL were observed in 2 patients but the HBV‐DNA levels became negative after NAA treatment. Patients who were negative for anti‐HBs showed a significantly higher incidence of HBV reactivation ( P  =   0.013). Conclusion: HBV reactivation occurred in 4.6% of RA patients with resolved HBV during the treatment with bDMARDs and the absence of anti‐HBs may be a risk factor for the reactivation of resolved HBV.